INNOVATION PROJECTS AS A BASE OF ECONOMIC DEVELOPMENT - Nesipbekov Ye.N.; Appakova G.N. (Academic Journal of Physical and Chemical Sciences, 2020)
The relatively weak support of technological enterprises, especially new ones, limits the efficiency of support measures oriented on its further development. Therefore, the State should interfere at the early stage to ensure the research and development of new projects having opportunities for further growth under the simultaneous control for funds not to be allocated for projects having no commercial potential. The support of the innovative projects favors the development and distribution of innovations, stimulates the innovative activity of enterprises and enhances the competitiveness of economy. The paper presents the critical analysis of the innovative projects support system in Kazakhstan. The paper provides the brief characteristics of the results of innovative policy of the country, considers the main instruments of the innovative projects support. Special attention in the paper is paid to the detailed analysis of the innovative projects received grant financing from the State. With that the analysis was made for quantitative indicators of innovative projects in industrial and regional fields, and for social and economic effect from its implementation. Basing on the represented material the paper provides recommendations and suggestions on improving the instruments of innovative projects stimulation in Kazakhstan and development of innovative potential of all participants of innovative process.